2017
DOI: 10.1097/bot.0000000000000664
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Posttraumatic Stress Disorder After Acute Orthopaedic Trauma: A Systematic Review and Meta-Analysis

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 51 publications
1
75
1
1
Order By: Relevance
“…Given methodological differences, it is difficult to directly compare our findings with other studies but the prevalence of anxiety and depression found in this study is slightly less than those reported for facial palsy (Fu et al, 2011) and facial paralysis (Pouwels et al, 2016). The findings suggest that facial scarring may result in a similar burden of depression but lower burden of anxiety than seen in acne patients (Lukaviciute et al, 2017), and a lower burden of depression compared to orthopaedic trauma patients (Muscatelli et al, 2016 (Egede, 2007). Patients with the latter conditions routinely receive more regular contact from health care providers and, therefore, there is greater opportunity to identify developing psychological comorbidity.…”
Section: Biascontrasting
confidence: 75%
“…Given methodological differences, it is difficult to directly compare our findings with other studies but the prevalence of anxiety and depression found in this study is slightly less than those reported for facial palsy (Fu et al, 2011) and facial paralysis (Pouwels et al, 2016). The findings suggest that facial scarring may result in a similar burden of depression but lower burden of anxiety than seen in acne patients (Lukaviciute et al, 2017), and a lower burden of depression compared to orthopaedic trauma patients (Muscatelli et al, 2016 (Egede, 2007). Patients with the latter conditions routinely receive more regular contact from health care providers and, therefore, there is greater opportunity to identify developing psychological comorbidity.…”
Section: Biascontrasting
confidence: 75%
“…While the disparities in research participation have been investigated in multiple clinical areas of research, there is a paucity of data specific to patients with traumatic injuries. Despite the psychological distress associated with a traumatic injury,11 refusal rates for trauma trials may be much lower than what has been reported in oncology literature. Several recently completed trials of orthopaedic trauma patients reported refusal rates of less than 15% 12–14…”
Section: Introductionmentioning
confidence: 76%
“…Interest in PTSD is increasing with a greater recognition of the deleterious effects of trauma and with the number of military personnel with amputations who experienced combat-related trauma (Doukas et al, 2013;Tennent et al, 2014). Critical reviews report higher rates of depression and post-traumatic stress disorder (PTSD) among patients with orthopaedic traumas (pooled estimates of 32.6% and 26.6%, respectively; Muscatelli et al, 2017) and hand trauma (Ladds, Redgrave, Hotton, & Lamyman, 2017) than observed among people in general. Studies have reported rates ranging from 20 to 47% of probable depression (Mckechnie & John, 2014), and 22.9-26% of possible PTSD (over a 6-month period; Phelps et al, 2008) among individuals with limb loss.…”
Section: Statement Of Contributionmentioning
confidence: 99%